In search of Carroll's Jeremiah - Le Roux, J. H. (Old Testament essays, 1994)
At the 1993 meeting of the South Africal society for Old Testament Studies time was devoted to Carroll's interpretation of Jeremiah and the manner in which he treated the so-called historical Jeremiah. This article is a brief discription of Carroll's views in this regard. It is stated that Carroll's commentary should not be used to search for the historical Jeremiah. Apparently such a person did not exist, or put differently: in the book of Jeremiah clear traces of such a historical person and his 'ipsissima verba ' are lacking. Carroll's commentary has other aims in mind amongst others to descriptionbe the ideologies at work in the formation of the book of Jeremiah.